Advanced data center infrastructure management system - Dang, Vince Xuan Vu (2018)
The purpose of this project is to develop the prototype infrastructure for the optimization and simulation functionalities of the Advance Data Center Infrastructure Management system. The optimization functionality, whose core algorithm was developed by the Green Data Center project’s researchers, is expected to minimize the energy consumption by dynamically manipulating the control parameters of the cooling units, while the simulation functionality, which is modelled after the National Super Computer Center (NSCC) data center, is expected to visualize of the air flow within the data center. These two engines, each contained in a reliable server, and a web application backend, altogether made up the three core components of the end-product infrastructure. With duplex communication, the two container servers can provide real-time monitoring and optimization data to the web application backend. Due to planned timeframe and the prototype nature of the infrastructure, the prototype doesn’t have advanced features such as encrypted connections for security, or load-balancing for scalability. It is expected that these features will be implemented should this prototype mature.